Asyum and non-refoulement in international law: an analysis - Eishan Jan, Mohammad Naqib (International Islamic University Malaysia, 2001)
Asylum seekeers, who claim to flee their state of orgin due to fear of persecution, normally find it difficult to enter into the territory of a foreign state and obtain asylum there as the state from which the asylum is sought follows the theory that the state has an absolute right to exclude all aliens including the asylum seekers. According to this theory the right to grant asylum is an attribute of the sovereign state and no individual alien is entitiled by right to be granted asylum. This theory has been adamantly supported and promulgated by governments around the world and in doing so they are often motivated by self-interest than considerations of humanity, and this provides a reason for thse seeking to combat persecution to insist upon the right of asylum. Although Grotius and Suarez are said to have recognized the right of asylum as the natural right of an individual entailing a corresponding state duty to grant asylum, this view has not yet been generally recognized under international law. Under international law, states have a right to grant asylum and a duty not to return refugees to states in which they would face persecution. This duty flows from the principle of non-refoulement- a principle well established in both conventional and customary international law. Although asylum seekers may not have a right to be granted permanent asylum, a right not to be rejected at the frontier or intercepted on the high seas is implied in the principle of non-refoulement and this in turn means that asylum seekers have an implied right to be allowed to enter the territory of the state from which they have sought refuge and this right is accompanied by the corresponding duty of the state to determine the merits of their request for asylum. The asylum seekers who legitimately need refuge or protection are entitled to receive it for as long as necessary to ensure that they will not to exposed to the risk of persecution in their states of orgin. States may, however, exercise their sovereign discretionary right to send back those individuals whose claim of fear of persecution is determined to be unfounded or who do not legitimately need protection.